Aktivitas Anti Candida albicans ATCC 14053 Sediaan Pasta Gigi Gel Ekstrak Daun Jengkol (Archidendron pauciflorum) dengan Kombinasi Na-CMC dan Karbomer: Activity of Anti-Candida albicans ATCC 14053 Toothpaste Gel Leaf Extract Jengkol (Archidendron pauciflorum) with Combination of Na-CMC and Carbomer - Aria Agustina Achsia; Ary Kristijono; Dara Pranidya Tilarso (Jurnal Sains dan Kesehatan, 2021)
Jengkol leaf extract can inhibit the growth of the fungus Candida albicans because it contains flavonoids, saponins, and tannins. Candida albicans species are most commonly found in the oral cavity that can cause various diseases in humans as canker sores and skin lesions. The purpose of this study was to formulate jengkol leaf extract into gel toothpaste preparations by distinguishing variations in the concentration of carbomer as a gelling agent. The research method used is experimental. Jengkol leaf samples extracted using the maceration method with 70% ethanol. The concentration of active substance used in each formula was 7.5% based on the preliminary test results and the carbomer concentration used was 0.5% in formula I, 1% in formula II, 1.5% in formula III, and 2% in formula IV. The physical stability test consists of organoleptic, homogeneity, spreadability, viscosity, pH, and high foam for 28 days of storage. Antifungal activity test using the disc diffusion method. Statistic analysis performed using the Shapiro-Wilk, Levene Statistics, and One Way Anova methods. During 28 days of keeping all formula homogeneous stable. The viscosity increased in each formulation due to differences in the concentration of carbomer used, the higher of carbomer the more viscous of the preparation, the pH, foam height of the formulation was stable and met the standard. The particles are evenly distributed so that the formulation colors and odors have stable. The result of the antifungal activity test of toothpaste gel extract of 7,5% jengkol leaf has inhibition of 11 mm. The increase in carbomer concentration showed a significant difference in each formula based on the One Way Anova statistical analysis (p <0.05) and the addition of carbomers to the formula showed stable viscosity and high foam. The most stable formula is the formula I with a carbomer concentration of 0.5%.